KARAKTERISTIK PERSONAL DAN KEPUASAN KERJA TENAGA EDUKATIF PERGURUAN TINGGI DI SURAKARTA - Sujadi Sujadi (Benefit: Jurnal Manajemen dan Bisnis, 2008)
The purpose of this study was to identify variables personal characteristic of education Staff University that explain the job satisfaction. If such variables areidentified, efforts can be made to eliminate or reduce the effects of those variables which lead to dissatisfaction and enhance those which lead to satisfaction. The participants were 52 respondents. Participants completed the short form of theMinnesota Satisfaction Questionnaire (MSQ)and modified with school and staffing survey questioner. Job satisfaction had six measures: general satisfaction, supervisor relation, peers, work environment, compensation and work it self. Personalcharacteristic variables that believed to explain job satisfaction of university staff education (age, gender, education, tenure, supervisor relations, structural position, and functional position) were analyzed through ordinary least square analysis to determine the effects of the independent variables job satisfaction. Results revealed university education staff is only marginally satisfied with their jobs. Education, functional occupation, and age of education staff signi ficantly influence of their overall job satisfaction